DOI: 10.14232/phd.1349
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of head and neck cancer patients after tumor treatment and subsequent maxillofacial rehabilitation

Abstract: III. Nagy J., Seres L., Novák P., Nagy K.: Implantáció a szájüregi rák miatt sugárkezelésben részesült betegeken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…Male respondents were somewhat older, M=58.50 ± 13.4 years as compared to female respondents, 52.88 ±15.1 years, but without any statistically significant difference, p=0.089. In the Gritz study the average age of patients was M=58.4 years, in the study of Nagy it was M=53.8 years, the Hassan study M=55 years, the Hassanein study M=58 years and in the Lam Tang study M=55.5 years ( 11 , 12 , 13 , 14 , 15 ), which is approximately similar age structure as in our respondents. In several studies the average age structure was slightly over 60 years of age: Nazar M=64.4 and Rogers M=62 years of age, whereas only one study had results for under 50 years of age, specifically Kazi study M=49.6 years ( 18 , 19 , 20 ).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Male respondents were somewhat older, M=58.50 ± 13.4 years as compared to female respondents, 52.88 ±15.1 years, but without any statistically significant difference, p=0.089. In the Gritz study the average age of patients was M=58.4 years, in the study of Nagy it was M=53.8 years, the Hassan study M=55 years, the Hassanein study M=58 years and in the Lam Tang study M=55.5 years ( 11 , 12 , 13 , 14 , 15 ), which is approximately similar age structure as in our respondents. In several studies the average age structure was slightly over 60 years of age: Nazar M=64.4 and Rogers M=62 years of age, whereas only one study had results for under 50 years of age, specifically Kazi study M=49.6 years ( 18 , 19 , 20 ).…”
Section: Discussionsupporting
confidence: 76%
“…We presented physical health components median values and concluded that problems related to swallowing (M=71.69±33.85), taste (M=68.88 ± 35.17) and saliva (M= 70.45±33.57) components had minimum score. In the studies of Nagy (Hungary) and Kazi the patients faced the biggest problem with chewing, whereas Rogers (USA) in his study showed that 45% of patients included in his study did not experience any chewing problems ( 12 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 95%
“…The scale consisted of 20 self-reported items with 15 questions of increasing anxiety level and 5 questions of decreasing anxiety level (Q. no. 5,9,13,17,19) . The score of each question ranged from 1 to 5 on a 5 point likert scale and higher scores indicated a better evaluation.…”
Section: Results (A) Data Collectionmentioning
confidence: 99%
“…Chemotherapy is defined as a concentrated and repeated treatment drug regimen for the management of cancer and its related symptoms, which is found to be associated with adverse reactions such as, hair loss, nausea, vomiting, and diarrhea, thereby leading to extended periods of treatment and repeated admissions to the hospital eventually affecting the QOL of cancer patients [14] . On the other hand, Radiation therapy which is often the final step in the multimodal treatment regimen for cancer might cause side-effects such as, skin pigmentation, destruction of salivary glands, severe problems related to eating, swallowing and speech, causing xerostomia, oral infections, dental caries, pain and discomfort [3,9] . Many aspects of QOL related to chemotherapy or radiotherapy treatment have been studied [1,22] .…”
Section: Introductionmentioning
confidence: 99%